Refusal and Adhesion: resistance between studies of cognition and theater education - Magela, André Luiz Lopes (Revista Brasileira de Estudos da Presença, 2021)
This article presents reflections on certain public education policy guidelines, oriented to the labor market and exemplified by Organisation for Economic Co-operation and Development (OECD) recommendations, concerning their influence on artistic education and, more precisely, theater education. It addresses existing problems in the field of education in Brazil and France, with emphasis on conceptual causes. In a possible contribution to debates on utilitarianism in theater education, the concept of resistance, present in Michel Foucault’s works, is used as mediator in the utilization of cognition studies to analyze the planning, practice and evaluation of theater classes in primary schools.